Persuasão e entretenimento: a publicidade-entretenimento se configura como estratégia comunicativa que resgata a retórica aristotélica - Figueiredo Neto, Celso (2008)
This doctorate work has as it is main objective the description and analysis of the phenomena called advertainment, which is a new communication strategy for advertising. The advertainment should be understood as a new paradigm in advertising since it has changed some of the fundamental processes of the advertising as we know it. Concerning the consumer, advertainment inverts the information flow, once it makes the consumer search, download, play and forward to his friends films from brands instead of being a simple receptor of advertising during the TV break. On the creative side, it is fundamental to build captivating stories to incentive consumers to forward these commercials to their friends. For this process to succeed it is needed a great deal of consumer involvement, only achieved if the advertising incorporates the rhetoric elements described by Aristotle in his elocucio, which is pathos, ethos and logos integrated within the message. In building messages which aggregate the Aristotle persuasive technics of captivating stories to be distributed throughout internet. With advertainment, advertising creates a new tool with high level of persuasiveness that allows brands to reach a different standard in communicating with their customers. Instead of transmitting information regarding products and incentive the purchase, advertising can be a source of entertainment, achieving a new status from the consumer point of view, becoming pleasant and desirable